2010
DOI: 10.1109/titb.2008.2010552
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Heterogeneous Classifier Ensembles for EMG Signal Decomposition Based on Classifier Agreement

Abstract: In this paper, we present a design methodology for integrating heterogeneous classifier ensembles by employing a diversity-based hybrid classifier fusion approach, whose aggregator module consists of two classifier combiners, to achieve an improved classification performance for motor unit potential classification during electromyographic (EMG) signal decomposition. Following the so-called overproduce and choose strategy to classifier ensemble combination, the developed system allows the construction of a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A MUP begins when its sample values exceed a threshold and ends when they fall below this threshold [54], [55], [59], [70], [71]. If a fixed-length window is chosen for analysis, the length of the window is set to include a fixed duration, typically 2.5 ms [1], [7], [19], [26], [27], [72], [74], [76][77][78], [81][82][83] or 6 ms [58], [66], [67]. Longer windows improve MUP representation, but will increase decomposition time.…”
Section: Signal Segmentation and Mup Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A MUP begins when its sample values exceed a threshold and ends when they fall below this threshold [54], [55], [59], [70], [71]. If a fixed-length window is chosen for analysis, the length of the window is set to include a fixed duration, typically 2.5 ms [1], [7], [19], [26], [27], [72], [74], [76][77][78], [81][82][83] or 6 ms [58], [66], [67]. Longer windows improve MUP representation, but will increase decomposition time.…”
Section: Signal Segmentation and Mup Detectionmentioning
confidence: 99%
“…Raw-data (time samples) and first-or second -derivative of time samples [1], [5][6][7], [19], [25], [27], [72], [74], [76][77][78][79][80], [82], [86], [87], power spectrum and Fourier transform coefficients [45], [49], [50], [62], wavelet coefficients [53][54][55], [59], [59], [79], [81], [83], [88][89][90][91][92][93][94], and principal components of wavelet coefficients [95] are features that have been used to represent and assign MUPs to MUPTs. Using power spectrum coefficients [62] or wavelet coefficients of MUPs decreases the dimensionality of the feature space and hence may improve the processing time.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MU discharges corresponding to a valid MUPT occur at regular intervals and in general, have a Gaussian-shaped IDI histogram while for invalid MUPTs the IDIs have large variations and will not have a Gaussian-shaped IDI histogram. Even though some researchers have demonstrated that the IDI distribution of a MU may not actually be Gaussian (De Luca & Forrest,1973;Matthews, 1996), for MUPTs of MUs that are consistently recruited, the Gaussian density is an appropriate approximation (Clamann, 1969;Stashuk, 1999;Moritz et al, 2005;Rasheed et al, 2010;. If an extracted MUPT represents the firing of a single MU and has suitably low percentage of FCEs (FCE rate), it has MU firing pattern validity.…”
Section: Mupt Validationmentioning
confidence: 99%
“…The study of aggregation operators is a large domain, supported by using aggregation concepts modeling uncertainty in distinct fields such as social, engineering or economical problems which are based on fuzzy logic (FL) [1,2,3,4]. Consequently, they have been applied to many fields of approximate reasoning [5], e.g.…”
Section: Introductionmentioning
confidence: 99%